TEACHING SCIENCE, CHEMISTRY AND BIOLOGY AT THE COLLEGE/UNIVERSITY LEVEL - Shaughnessy, Michael F.; Yan, Juchao (Acta Scientiae et Intellectus, 2024)
When college students arrive in science classes, some are woefully unprepared, some are minimally prepared, and some, while well educated in high school have forgotten many of the basics in terms of basic science, basic scientific reasoning, and basic scientific procedures. This paper examines some of these issues, reviews some of the main areas of concern and delves into issues of formative evaluation and the issue of pre-requisite courses.